2013
DOI: 10.1128/jcm.02780-12
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Based Method with Performance Comparable to That of PCR-Based Methods for Detection of Group B Streptococcus in Screening Samples from Pregnant Women

Abstract: We compared five approaches for group B streptococcus (GBS) detection: three culture-based methods and two methods using broth-enhanced real-time PCR. Carrot broth-enhanced subculture to GBS Detect (Hardy Diagnostics, Santa Maria, CA) exhibited sensitivity and specificity comparable to carrot broth-and LIM broth-enhanced real-time PCRs. G roup B streptococcus (GBS) colonization during pregnancy has been implicated as a major risk factor for severe neonatal infections, including sepsis, pneumonia, and meningiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
2
18
1
1
Order By: Relevance
“…A commonly cited drawback of incorporation of molecular (27). The researchers demonstrated that enriched PCR methods could yield quicker results, but there was no significant improvement in GBS detection.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly cited drawback of incorporation of molecular (27). The researchers demonstrated that enriched PCR methods could yield quicker results, but there was no significant improvement in GBS detection.…”
Section: Discussionmentioning
confidence: 99%
“…Performance of qPCR directly with rectovaginal samples missed 3% of the cases that were detected by using pre-enrichment prior to either CM culture or qPCR, although the bacterial inoculum size was small for these women. Berg et al compared five different methods of genital GBS detection that included three culture-based methods, including chromogenic culture with Northeast Laboratory GBS agar (Northeast Laboratory Services, Winslow, ME), carrot broth-enhanced subculture to GBS Detect (Hardy Diagnostics), and carrot broth-and Lim broth-enhanced real-time PCRs, as well as routine Strep B Carrot Broth culture (22). Carrot broth-enhanced subculture to GBS Direct chromogenic medium had performance comparable to that of broth-enhanced qPCR, and either method had a higher sensitivity than routine culture.…”
Section: Discussionmentioning
confidence: 99%
“…Otros autores afirman que el tamizaje debe enfocarse en las pruebas no moleculares, como subcultivo de caldo de zanahoria mejorado, el cual consiste en un medio rico en nutrientes que permite el crecimiento selectivo del SGB y posterior identificación por la gamma hemólisis que provoca en este medio; cabe resaltar que tiene características de rendimiento aceptables para la detección y aislamiento del SGB con una sensibilidad del 82.5% y una especificidad hasta del 100% (20).…”
Section: Tamizajeunclassified